Design Space Exploration zur multikriteriellen Optimierung elektrischer Sportwagenantriebsstränge: Variation von Topologie und Komponenteneigenschaften zur Steigerung von Fahrleistungen und Tank-to-Wheel Wirkungsgrad - Vaillant, Moritz (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2016)
The link between drivetrain topology and energy consumption for all electric sports cars is analyzed. The drivetrain topology is varied along with the characteristics of the used components to find a system optimum instead of a component optimum. Design Space Exploration is used to explore the interactions between drivetrain topologies and component characteristics for different sports cars and driving cycles. Finally, design rules for efficient and high-performing drivetrains were derived.